한국어 발표 교육 관련 연구 동향 분석 - 김지현; 조희선 (Foreign Languages Education, 30(4), 2023)
The purpose of this study is to analyze 118 studies in the field of Korean presentation education conducted between 2005 and January 2023 and to provide insight into the future direction of research in this area. The study utilized Topic modeling and direct researcher analysis methods to examine Korean presentation education research materials. The analysis revealed a steady increase in research on Korean presentation education, with high frequency keywords such as ‘academic’, ‘purpose’, ‘discourse’, and ‘class’ indicating that research has been conducted on these topics. Furthermore, the Topic modeling analysis revealed that many studies have focused on ‘study on the analysis of aspects and the use of strategies in presentation discourse’ and ‘study on the use of presentation classes by learners’, particularly for Chinese native learners. In terms of research methods, the analysis conducted through direct researcher analysis showed that the most common methods used were ‘dialogue analysis’ and ‘survey research’, and single research methods were utilized more frequently than mixed methods. Based on these findings, this study suggests that future research should focus on Korean presentation education for language learners with various purposes and employ a variety of research methods.